Determinants of Patient Loyalty: A Systematic Review - Ubery, Yulinda Ferdiana; Ernawaty, Ernawaty (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT Patient loyalty is the key to business success for healthcare providers as well as patient health outcomes. This research aims to identify factors that determine patient loyalty using a systematic review study. Articles published in the last 5 years in Proquest, Google Scholar, and PubMed databases were systematically reviewed. Eight articles that met the inclusion and exclusion criteria were selected for further review. Findings regarding the determinants of patient loyalty to healthcare organizations were systematically synthesized. Publications on factors that determine patient loyalty to screening health care providers and 20 articles were included in this study. Twenty articles explore 14 determinants of patient loyalty such as patient satisfaction, quality, value, hospital brand image, trust, commitment, CRM, patient experience, service delivery, relationship marketing and word-of-mouth (WoM), CSR, perceived value, implementation of innovation, and environmental services. This review identified and modeled the determinants of patient loyalty to healthcare providers. Further research should consider extending this research to general hospitals, clinics and health centers. clinics and health centers to identify the most dominant factors of interest. Keywords: Health Services, Patient Loyalty, Systematic Review